Pengaruh Kemandirian Belajar terhadap Kemampuan Pemecahan Masalah Matematika Siswa Kelas VIII SMP Negeri 7 Lubuk Basung - Juninda Ermita (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This research is motivated by students experiencing difficulties in solving problems in the form of descriptions and students' problem solving abilities in learning mathematics are still low at SMP Negeri 7 Lubuk Basung in the 2020/2021 academic year, this is indicated by the lack of independence of students in learning mathematics. The purpose of this study was to determine whether there was a significant effect of learning independence on the mathematical problem solving abilities of eighth grade students of SMP Negeri 7 Lubuk Basung in the 2020/2021 academic year. The statistical analysis technique used in this research is regression analysis. The results of this study obtained a correlation coefficient value of rxy = 0.543 and a determinant coefficient value of KD = 29.4849% From hypothesis testing, for the significant effect of learning independence on mathematical problem solving abilities of class VIII students of SMP Negeri 7 Lubuk Basung obtained Zcount = 3.801 and Ztable = 1.96 at 0.05 confidence. The regression equation between learning independence and mathematical problem solving ability of eighth grade students of SMP Negeri 7 Lubuk Basung Y = -30.009 + 1.126X. If Zcount > Ztable, then the research hypothesis is accepted. This means that there is a significant effect of learning independence on students' mathematical problem solving abilities.Penelitian ini dilatarbelakangi oleh siswa mengalami kesulitan dalam menyelesaikan soal berbentuk uraian dan kemampuan pemecahan masalah siswa dalam pembelajaran matematika tergolong masih rendah di SMP Negeri 7 Lubuk Basung Tahun Pelajaran 2020/2021, hal ini diindikasikan oleh kurang mandirinya siswa dalam pembelajaran matematika. Tujuan dilaksanakan penelitian ini untuk mengetahui apakah terdapat pengaruh signifikan kemandirian belajar terhadap kemampuan pemecahan masalah matematika siswa kelas VIII SMP Negeri 7 Lubuk Basung Tahun Pelajaran 2020/2021. Teknik analisis statistik penelitian yang digunakan adalah analisis regresi. Hasil penelitian ini diperoleh nilai koefisien korelasi sebesar rxy = 0.543 dan nilai koefisien determinan sebesar KD = 29.4849% Dari pengujian hipotesis, untuk pengaruh signifikan kemandirian belajar terhadap kemampuan pemecahan masalah matematika siswa kelas VIII SMP Negeri 7 Lubuk Basung diperoleh Zhitung = 3.801 dan Ztabel = 1.96 pada kepercayaan 0.05. Persamaan regresi antara kemandirian belajar terhadap kemampuan pemecahan masalah matematika siswa kelas VIII SMP Negeri 7 Lubuk Basung Y = -30.009 + 1.126X. Jika Zhitung > Ztabel , maka hipotesis penelitian diterima. Artinya terdapat pengaruh yang signifikan kemandirian belajar terhadap kemampuan pemecahan masalah matematika siswa.